(untitled) (Indian Journal of Public Health Research & Development, 2023)
Tele-dentistry has a history going back to 1994. The main concept of tele-dentistry proposes the application of information and communication technologies (ICT) to facilitate oral healthcare for geographically distant patients and/or practitioners. It also allows dental professionals to communicate with one another over long distances. It not only has the potential to increase accessibility of specialists, but also decreases time and cost associated with speciality consultations. The aim of this article is to present an overview of the uses of information and communication technologies in oral health.